Absenteeism and firm performance: Evidence from retail - Jakob Alfitian (Max Planck Institute for Research on Collective Goods, 2025)
This study examines the relationship between absenteeism and firm performance using data on 1,387 stores of a retail chain, combined with public health data, covering a 36-month period. Crucially, the relationship between absenteeism and sales is not monotonic. Instead, it exhibits an inverted U-shape. This indicates that a reduction in absenteeism does not necessarily result in improved firm performance. In fact, moderate absenteeism is associated with higher sales than perfect attendance. Moreover, if the actual level of absenteeism is below the level expected due to the regional acute spread of respiratory disease, this is associated with lower sales than if both align. A similar relationship is also observed between absenteeism and measures of service quality. Endogeneity concerns are addressed using fixed effects regression and instrumental variable estimation. In conclusion, the results demonstrate that absenteeism is not generally detrimental to firm performance. It is therefore not advisable to attempt to avoid absenteeism altogether.
hdl:21.11116/0000-0010-8284-5
Keywords: 330; absenteeism; firm performance; service quality; retail chain; Germany; Fehlzeit; Unternehmenserfolg; Dienstleistungsqualität; Handelskette; Deutschland